A case report of a novel compound heterozygous mutation in a Brazilian patient with deficiency of Interleukin-1 receptor antagonist (DIRA) - Leonardo Oliveira Mendonça; Alice Grossi; Francesco Caroli; Robson Aguiar de Oliveira; Jorge Kalil; Fabio Fernandes Morato Castro; Alessandra Pontillo; Isabella Ceccherini; Myrthes Anna Maragna Toledo Barros; Marco Gattorno (BMC, 2020)
Abstract Background Deficiency of the natural antagonist of interleukin-1 was first described in 2009 and so far 20 patients has been reported. In Brazil just two cases have been reported both carrying the same homozygous 15 bp deletion. Blocking interleukin-1 has changed rate survival for DIRA patients. The use of anakinra and rilonacept has been reported safe and efficient, whereas the selective blockade of interleukin-1 beta, using the monoclonal antibody canakinumab has been reported in a single case only. Case presentation Here we report a case of a 7 years old Brazilian boy that presented with recurrent episodes of systemic inflammation with severe disabling osteomyelitis with mild pustular skin rash. A Next Generation Sequencing gene panel allowed to detect two pathogenic mutations in the IL1RN gene, described in compound heterozygosity. Corticosteroids was effective in controlling inflammation and anti-IL1 beta blocker triggered disease flare. Complete clinical control could be achieved using IL-1 receptor antagonist. Conclusions DIRA is a severe, life threatening autoinflammatory condition with low numbers of patients described all over the world. The mutation p.Asp72_Ile76del in IL1RN is presented in all Brazilian DIRA patients already described and p.Q45* (rs1019766125) is a new mutation affecting the IL1RN gene. Following the pathogenesis of DIRA, blocking both subunits of interleukin one as well as antagonizing the receptor using anakinra or rilonacept seems to be effective. There is just one report using canakinumab for the treatment of DIRA and this is the first report of disease flare using this drug.